Professional stereotypes among specialties and fields of work within the veterinary community. (7th March 2022) - Agathou, Sylvia; Stratis, Andreas; Routh, Jennifer; Paramasivam, Sharmini J.
Abstract: Background: Medical specialties hold varying degrees of prestige, stemming from the existence of stereotypes among them. These have been shown to lead to prejudice against specific specialists, which not only influences career choices but also affects the perception of equality among specialties. Method: The aim of the research was to determine the presence of stereotypes in the UK veterinary community. Using an online questionnaire, participants were asked to provide an adjective that best characterises 15 specialties, in addition to their perceptions on prestige and gender association. Word cloud analysis coupled with sentiment analysis in Python using the language processing software Natural Language Toolkit (NLTK) was used to assess sentiments with respect to the adjectives. Results: There were 665 questionnaire respondents, and there was evidence of their construction of specialty‐specific stereotypes. Some specialties were perceived more negatively than others, including equine general practitioners, surgeons, pathologists, dermatologists and public health veterinarians/epidemiologists. Gender bias was identified within this study, most prominently within production animal and behavioural medicine veterinarians. The most prestigious specialties were neurology, surgery and cardiology. Conclusion: Specialty‐specific stereotypes exist within the veterinary community. Acknowledging their existence is a first step to recognising the influence they have on career choices.